2006
DOI: 10.1095/biolreprod.105.050278
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Spermatogenesis and Male Fertility by Transplantation of Dispersed Testicular Cells in the Chicken1

Abstract: Transplantation of male germ cells into sterilized recipients has been widely used in mammals for conventional breeding and transgenesis purposes. This study presents a workable approach for germ cell transplantation between male chickens. Testicular cells from adult and prepubertal donors were dispersed and transplanted by injection directly into the testes of recipient males sterilized by repeated gamma irradiation. We describe the repopulation of the recipient seminiferous epithelium up to the production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 51 publications
3
53
0
8
Order By: Relevance
“…This efficiency is comparable with animals transplanted in parallel directly with uninfected testicular cells, but a bit lower in comparison with our previous transplantation experiments (Trefil et al 2006), where the efficiency reached 50%. Small numbers of birds used in these experiments might cause such differences.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This efficiency is comparable with animals transplanted in parallel directly with uninfected testicular cells, but a bit lower in comparison with our previous transplantation experiments (Trefil et al 2006), where the efficiency reached 50%. Small numbers of birds used in these experiments might cause such differences.…”
Section: Discussionsupporting
confidence: 78%
“…Trefil et al (2006) have shown previously that this transplantation in chickens resulted in the re-colonization of the seminiferous epithelium with partial resumption of spermatogenesis and production of viable and fertilization-competent spermatozoa. In this report, we have continued our studies and observed the functional recovery of exogenous spermatogenesis after transplantation of in vitro infected testicular cell mixture.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although most studies have been performed in rodents, germ cell transplantation has also been applied to non-rodent species as pigs, goats, cattle, monkeys and recently fish and chickens (Honaramooz et al, 2002a(Honaramooz et al, ,b, 2003Schlatt et al, 2002;Izadyar et al, 2003b;Takeuchi et al, 2003;Yoshizaki et al, 2005;Lee et al, 2006;Mikkola et al, 2006;Okutsu et al 2006;Trefil et al 2006), as reviewed by Dobrinski, (2008). The first hurdle found when germ cell transplantation was applied to livestock species was the differences in testicular anatomy and physiology.…”
Section: Sscs Transplantation and Transgenesismentioning
confidence: 99%